Editorial: Cross-Perspectives on Digital Transformation, Artificial Intelligence, and Sociolinguistic Dynamics - Aniss MOUMEN (Moroccan Journal of Quantitative and Qualitative Research)
In a constantly evolving world, the impact of digitalization and new technologies is felt at all levels of society, from public management to business performance, sociolinguistic dynamics, and sustainable investment. The articles studied in this issue address several facets of this transformation and shed light on current trends and future challenges.